Partial loss of MCU mitigates pathology in vivo across a diverse range of neurodegenerative disease models. - Twyning, M.J.; Tufi, R.; Gleeson, T.P.; Kolodziej, K.M.; Campesan, S.; Terriente-Felix, A.; Collins, L.; De Lazzari, F.; Giorgini, F.; Whitworth, A.J. (Cell reports, 2024)
Mitochondrial calcium (Ca[2+]) uptake augments metabolic processes and buffers cytosolic Ca[2+] levels; however, excessive mitochondrial Ca[2+] can cause cell death. Disrupted mitochondrial function and Ca[2+] homeostasis are linked to numerous neurodegenerative diseases (NDs), but the impact of mitochondrial Ca[2+] disruption is not well understood. Here, we show that Drosophila models of multiple NDs (Parkinson's, Huntington's, Alzheimer's, and frontotemporal dementia) reveal a consistent increase in neuronal mitochondrial Ca[2+] levels, as well as reduced mitochondrial Ca[2+] buffering capacity, associated with increased mitochondria-endoplasmic reticulum contact sites (MERCs). Importantly, loss of the mitochondrial Ca[2+] uptake channel MCU or overexpression of the efflux channel NCLX robustly suppresses key pathological phenotypes across these ND models. Thus, mitochondrial Ca[2+] imbalance is a common feature of diverse NDs in vivo and is an important contributor to the disease pathogenesis. The broad beneficial effects from partial loss of MCU across these models presents a common, druggable target for therapeutic intervention.